A new approach for disclosure control in the IAB Establishment Panel: multiple imputation for a better data access - Jörg Drechsler; Agnes Dundler; Stefan Bender; Susanne Rässler; Thomas Zwick (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2007)
For micro-datasets considered for release as scientific or public use files, statistical agencies have to face the dilemma of guaranteeing the confidentiality of survey respondents on the one hand and offering sufficiently detailed data on the other hand. For that reason a variety of methods to guarantee disclosure control is discussed in the literature. In this paper, we present an application of Rubin's (1993) idea to generate synthetic datasets from existing confidential survey data for public release. We use a set of variables from the 1997 wave of the German IAB Establishment Panel and evaluate the quality of the approach by comparing results from an analysis by Zwick (2005) with the original data with the results we achieve for the same analysis run on the dataset after the imputation procedure. The comparison shows that valid inferences can be obtained using the synthetic datasets in this context, while confidentiality is guaranteed for the survey participants.
Keywords: C11; C13; C49; C53; 330; IAB-Betriebspanel; Datensicherheit; Datenschutz; Datenaufbereitung; Anonymität; Mikrodaten; Panel; Datenschutz; Vertrauen; Statistik der Unternehmen und Arbeitsstätten; Deutschland